1989
DOI: 10.3133/ofr89178
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings of workshop XLIV; geological, geophysical, and tectonic setting of the Cascade Range

Abstract: VllNorthern California through Oregon and Washington to British Columbia. The intellectual scope was as broad and interdisciplinary as possible, with participants representing the fields of geology, heat flow, seismology, igneous petrology, hydrology, electromagnetic geophysics, magnetics, water geochemistry, gravity, paleomagnetism, and tectonics.The conference was organized around three major themes:Variations in tectonics, geophysical signature, and magmatism along the length of the Cascade volcanic arc.Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 250 publications
(519 reference statements)
0
4
0
Order By: Relevance
“…There is a significant variation in rates of modern seismicity along the Cascade Range, with the area south of Mount Hood in Oregon being quiet compared to other parts of the Cascades (Weaver, 1989). For example, a four station array along with an ultraportable outlier station operated in the summer of 1970 at Crater Lake found that there were fewer small events at Crater Lake than at Mount Hood and that no recorded events were deeper than 12 km (Westhusing, 1973).…”
Section: Seismicitymentioning
confidence: 99%
“…There is a significant variation in rates of modern seismicity along the Cascade Range, with the area south of Mount Hood in Oregon being quiet compared to other parts of the Cascades (Weaver, 1989). For example, a four station array along with an ultraportable outlier station operated in the summer of 1970 at Crater Lake found that there were fewer small events at Crater Lake than at Mount Hood and that no recorded events were deeper than 12 km (Westhusing, 1973).…”
Section: Seismicitymentioning
confidence: 99%
“…There is a significant variation in rates of seismicity along the Cascade Range, with the area south of Mount Hood in Oregon being particularly quiet compared to other parts of the Cascades (Weaver, 1989). A four station array along with an ultraportable outlier station operated in the summer of 1970 at Crater Lake found that there were fewer small events at Crater Lake than at Mount Hood (Westhusing, 1973).…”
Section: Seismicity Of Crater Lake and Vicinitymentioning
confidence: 99%
“…The climactic eruption took place over a few days, toward the end of which the caldera collapsed. This eruption produced a classic, compositionally zoned pyroclastic deposit that represents the rather orderly venting of a shallow, stratified magma body (Druitt and Bacon, 1986, 1989Bacon and Druitt, 1988). Pumiceous pyroclastic-flow deposits fill valleys around Mount Mazama to depths of -100 m ( Figure 2) and extend as much as 70 km from the caldera.…”
Section: The Last 30000 Yearsmentioning
confidence: 99%
“…Here, we combined a database of mapped Quaternary vents, surface topography, and diverse geophysical data sets within the Cascades arc (western North America) to probe relations between volcanism and underlying crustal structure. Building on prior efforts to synthesize geophysical (e.g., Weaver et al, 1989;Wells et al, 1998;Till et al, 2019) and geologic (e.g., Guffanti and Weaver, 1988;Hildreth, 2007) data in the Cascades arc, we analyzed (1) arc-scale relations among geophysical data sets associated with magmatism; (2) the extent to which volcanoes match geophysical subsurface magmatic signatures; and (3) temporal variations in these relations during the Quaternary.…”
Section: Introductionmentioning
confidence: 99%